Utilizing ion mobility and tandem mass spectrometry to evaluate the structure and behaviour of multimeric cyclodextrin complexes - Berland, Kevin; Renaud, Justin B.; Mayer, Paul M. (Université d'Ottawa | University of Ottawa, 2015)
Characterizing noncovalent complexes of molecular dimers and higher complexes using tandem mass spectrometry (MS/MS) can be hindered due to spectral overlap in both the MS and the MS/MS. We investigated the structures and dissociation energetics of multimeric β-cyclodextrin (β-CD) complexes alone or with substrates using combinations of ion mobility spectrometry (IMS), MS/MS, and Rice–Ramsperger–Kassel–Marcus (RRKM) unimolecular rate modelling. The doubly charged β-CD dimers ([(β-CD)2 – 2H+]2−) dissociate to two [β-CD – H+]− ions with the same m/z. IMS was used to separate source generated [(β-CD)2 – 2H+]2− from [β-CD – H+]− and the extent of [(β-CD)2 – 2H+]2− dissociation versus collision energy was determined by modelling changes in the ion’s isotopic profile. The RRKM derived critical energy (E0) for dissociation of [(β-CD)2 – H+]− and [(β-CD)2 – 2H+]2− were 1.85 ± 0.11 eV and 1.79 ± 0.09 eV, respectively, corresponding to a slight decrease in complex stability due to increased charge–charge repulsion in the dianion. This approach was extended to include dimeric complexes complexed to 4,4′-(propane-1,3-diyl) dibenzoic acid (PDDA) and ibuprofen (Ibu).
Keywords: cyclodextrin; ion mobility; Rice–Ramsperger–Kassel–Marcus (RRKM); ion dissociation; inclusion complex; tandem mass spectrometry